Ekofeminisme dalam Novel Dia adalah Kakakku Karya Tere Liye: Kajian Ekofeminisme Vandana Shiva - Rihada Aisy; Sarwiji Suwandi (Simpati, 2026)
This study aims to describe the representation of ecofeminist values ​​in Tere Liye's novel "Dia adalah Kakakku". This is a qualitative descriptive study using a content analysis approach. The research data consist of sentences and paragraphs sourced from Tere Liye's novel "Dia adalah Kakakku". The sampling technique used was purposive sampling. Data collection was conducted through document analysis. Data analysis was conducted using data reduction, data presentation, and conclusion drawing procedures. The results of this study revealed 50 data points on Vandana Shiva's ecofeminist values, divided into six aspects. The dominant finding is the value of the relationship between women and nature, which demonstrates the closeness, dependence, and responsibility of female characters towards the environment through the wise and sustainable use of natural resources. Other aspects include feminine values, protecting nature, environmental conditions, science and nature, and natural/local knowledge. From the narratives in the novel, ecofeminist values ​​are represented through women's concern for and role in managing and preserving nature.